Tradisi Ritual Kematian Islam Kejawen Ditinjau Dari Sosiologi Hukum Islam - Mahmudah, Nurul; Saputera, Abdur Rahman Adi (Analisis: Jurnal Studi Keislaman, 2019)
The arrival of Islam on Java gave a new color to the ceremonies in the Javanese tradition, including the death ceremony. Although it is now "Islamic", some Muslims still reject the tahlilan tradition. They consider him to be an unclean bid'ah. Because the tahlilan tradition has never been disyariatkat by Allah and has never been done by the prophet and his friend. While those who support the tahlilan tradition assume that this tradition is tantamount to the teachings of reciting the holy verses of the Koran for the dead, which is an Islamic recommendation. In addition, the tahlilan tradition also contains social concerns. This paper aims to examine how the ritual tradition of death in Kejawen Islam. The researcher used a historical analysis approach. The ritual tradition of the death of Islam Kejawen is the reading of prayer for the deceased whose implementation is adapted to the Javanese cultural heritage before the arrival of Islam. the essence of this ritual is to foster the spirit of da'wah, build togetherness, draw closer to Allah through dzikir, prayer, and recitation of the Qur'an. So if this is the meaning of tahlilan, even though the practice is not in the Shari'a and the Sunnah, according to the researchers it is good to do it.